PROMOTING A CITIZEN-ORIENTED POLICE FORCE: REFLECTIONS ON THE HISTORICAL ROLE OF CARLOS MAGNO NAZARETH CERQUEIRA AND THE CHALLENGE OF TRAINING MILITARY POLICE OFFICERS TO SERVE VULNERABLE GROUPS - Castiajo, Daniel (Revista Gênero e Interdisciplinaridade, 2026)
This paper proposes a reflection on the fundamental texts of the "Police Tomorrow" collection, focusing on the intersection between police activity and gender issues, children, and adolescents at social risk in the State of Rio de Janeiro. The works discuss female victimization, analyzing both domestic violence and the challenges faced by female detainees under state custody, as well as primary prevention actions. The methodology employed is based on an interdisciplinary approach that articulates bibliographic research and content analysis. The theoretical framework includes Nazareth Cerqueira, Nilo Batista, and recent documents from the Brazilian Forum on Public Security. The aim is to analyze which approaches can be adopted as strategies for the professional improvement of military police officers engaged in serving women, children, and adolescents who are victims of violence. Preliminary results indicate that the aforementioned texts pay homage to Colonel Carlos Magno Nazareth Cerqueira, exploring his vision and efforts to propose a more humanized and "citizen-oriented" police force. From an academic and institutional perspective, the materials offer guidelines for the use of force and respect for human rights. In short, the sources serve as a theoretical and practical guide for the reform of public security institutions in Brazil. However, it is worth noting that, in contemporary times, the discourse that reinforces a "warrior ethos" still prevails, which historically perpetuates itself in the cultural context within the barracks and manifests itself in daily police work. This makes the mission of forming a "citizen police force" challenging in terms of knowledge production, offering plausible alternatives for the relationship between the police and society, as well as the promotion of human rights.